Polyphenol blend enhances zootechnical performance, improves meat quality, and reduces the severity of wooden breast in broiler chickens - de Castilho Heiss, Vivian Aparecida Rios; Burbarelli, Maria Fernanda de Castro; Przybulinski, Bruna Barreto; Garcia, Letícia Cuer; Vieira, João Ricardo Rodrigues Ferreira; Garcia, Rodrigo Garófallo; Caldara, Fabiana Ribeiro; Santin, Elizabeth; Cardoso, Claudia Andrea Lima; Komiyama, Claudia Marie (Frontiers in Veterinary Science, 2025)
This study investigated the effects of a commercial polyphenol blend on broiler performance, meat quality, carcass traits, and the incidence of pectoral myopathies. Broilers (1–42 days old) were allocated to four treatments: T1 (control, basal diet), T2 (250 g/ton polyphenol blend), T3 (500 g/ton), and T4 (1,000 g/ton), with eight replicates of 40 birds each. All diets were corn-soy based, isonutritional, and formulated to meet age-specific nutritional requirements. Parameters assessed at 21, 28, 35, and 42 days included antioxidant potential, growth performance, myopathy incidence, carcass yield, allometric growth, muscle morphometry, meat quality, and lipid profile. Optimal performance was observed at a supplementation level of 514 g/ton of polyphenols. While carcass yield remained unaffected, birds fed 500 g/ton exhibited delayed breast growth relative to other body parts, suggesting modulated allometric growth. Polyphenol supplementation reduced breast muscle fiber size, increased fiber density, and lowered the severity of wooden breast without influencing the incidence of white striping. Improved meat tenderness was evident through reduced cooking weight loss and enhanced shear force. Antioxidant status improved in plasma, muscle, and liver tissues, and the muscle lipid profile was favorably altered. In conclusion, the polyphenol blend enhanced broiler zootechnical performance, alleviated wooden breast severity, and improved meat quality and tenderness.